Деякі аспекти формування архітектоніки та художньо-естетичного образу у традиційному народному будівництві Карпатського регіону - Матійчук, М. (Матеріали до української етнології, 2007)
In this investigation was examined the system of proportional dependencies in national architecture and the influence of traditional cut material and technology on the formation of architectonics and artistic-aesthetic form in national construction of the Ukrainian Carpathians. The architectonics of national construction are dependent on the correlation of basic visible masses of building - walls and roofs. The roof, like a dominating report, has a main role in forming the aesthetics of the building. Traditional materials for covering (straw and chopped board) dictated suitable technologies of configuration of the roof, which, in its turn, influenced the proportion, which was very important for the entirety and artistic-aesthetic form of the building.